Two Vigna Species Native to Argentina with Ornamental Potential - Hoc, Patricia Susana (2013)
Vigna candida (Vell.) Maréchal, Mascherpa and Stainier and V. adenantha (G.F.W. Meyer) Maréchal, Mascherpa and Stainier have potential as ornamentals and could be used as forage crops in warm areas. They are scandent, stolonate and pluri-annual. In both species the flowering period begins in springtime and last until autumn. The flowers are flag blossoms, disposed in 5-10-flowered racemes of 10 cm long. The standard and the keel are white, the wings are white with violet nectar guides; a variation in the color pattern of these petals occur between the species. During the anthesis, that lasts 1-2 days, an anular nectary that surround the ovary secrete the nectar offered as reward. Legitimate flower visitors are species of Xylocopa, Centris and Bombus (Hymenoptera), because of only these individuals can trigger the system of pollen transfer; also, nectar and pollen thieves or robbers were detected but did not affect the reproductive success. In V. candida, aroma is also emitted as other secondary attractant. Experiments of controlled pollinations were carried out in order to know the reproductive system of each species. V. adenantha is self-compatible but the reproductive success reach the 100% when pollinators visit the flowers, oppositely, in V. candida, which is self-incompatible, if pollinators do not work, fruits and seeds cannot be produced. Because of the growing pattern, phenology, the beautiful and conspicuous flowers, and the nitrifying capacity, both species should be appreciated as ornamentals in warm or temperate areas, even in flooded land.